Avaliaç\~ao econômica de experiências nacionais e internacionais de subsídios cruzados no setor de transportes terrestres - Rennaly Patricio Sousa; Edison Benedito Da Silva Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This study seeks, in a preliminary way, to evaluate national and international experiences in the use of cross-subsidies applied to transport infrastructure concessions with less commitment from the public budget. Alternatives to the adopted concession models are analyzed, such as the use of public funds, the concession through bundles of projects and clearing house systems, in order to identify the specificities, advantages and disadvantages of the selected models. We conclude that the improvement and strengthening of the Brazilian institutional framework with regard to fiscal management is essential to ensure the success of concession models involving cross-subsidy with the use of public resources.
Keywords: G32; L98; R42; 330; transportation; cross-subsidization; public funds